1979
DOI: 10.1177/0022022179101001
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Cultural Convergence

Abstract: Past research on individual modernity has concentrated on identification of the antecedents of more modern patterns of thinking, valuing, and behaving. The present study attempts to take a next step in this research tradition, to determine whether value modernization also implies cross-cultural value convergence. Data were obtained from samples at four levels of industry in each of three countries (Ghana, India, and Brazil) on 22 questions designed to assess modernity in values. Responses were submitted to a "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Child and Kieser (1979), for example, compared organizational and managerial roles between British and West German companies but did not find complete support for the Convergence Hypothesis argument. Fliegel et al (1979), likewise, found mixed support, reporting that whereas oil refinery workers across countries in the sample had similar values, farmers did not. Bird and Kotha (1994, p. 97), in a study comparing American versus Japanese managerial perceptions of advanced manufacturing technologies, found support for the Convergence Hypothesis argument, noting that “… as influential technologies diffuse widely, they become accepted and managers’ assessments of their importance do, in fact, converge…”.…”
Section: Convergence Hypothesis Versus National Specificity Argumentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Child and Kieser (1979), for example, compared organizational and managerial roles between British and West German companies but did not find complete support for the Convergence Hypothesis argument. Fliegel et al (1979), likewise, found mixed support, reporting that whereas oil refinery workers across countries in the sample had similar values, farmers did not. Bird and Kotha (1994, p. 97), in a study comparing American versus Japanese managerial perceptions of advanced manufacturing technologies, found support for the Convergence Hypothesis argument, noting that “… as influential technologies diffuse widely, they become accepted and managers’ assessments of their importance do, in fact, converge…”.…”
Section: Convergence Hypothesis Versus National Specificity Argumentsmentioning
confidence: 92%
“…Hence, as the transfer of modern industrial technology occurs across nations, these nations would be compelled to align their socio‐economic and socio‐political environments to the industrial technology being transferred (Cole, 1973). Such alignments would consequently undermine a nation's adherence to ideological principles, beliefs, and dogmas (Webber, 1969, p. 78), “… placing demands on individuals to alter modes of thinking and behaving…” (Fliegel et al, 1979, p. 4) that, in turn, would foster the development of similar human nature and social behavior across nations (Dore, 1973; Form, 1979). Eventually, the imperative of industrialization would result in different nations possessing not only similar industrial technology but also similar infrastructures created from the same organizing principles (Lincoln et al, 1986), as well as individuals who evolve to become “… more homogeneous in outlook, habits, values, and beliefs” (Lincoln and Kalleberg, 1990, p. 20).…”
Section: Convergence Hypothesis Versus National Specificity Argumentsmentioning
confidence: 99%
“…A comparison of managerial values across the US, Australia, Japan, South Korea, and India, inspired by the work of Kerr and associates, reported that “even among countries where there are common past cultural experiences, little or no similarity was found in the present study” (Whitely & England, 1977, p. 452). Fliegel et al (1979) found no evidence that the implementation of modern technologies cause convergence of values across cultures. Priem et al (2000) concluded that some values converge with industrialization, while others remain divergent.…”
Section: Introductionmentioning
confidence: 93%
“…Interesting as the topic of the evolution of cultural distances across the globe may be, there is a scarcity of longitudinal studies comparing a sample of countries from all continents that represent the most important cultural variation across modern nations. The existing literature (Bergiel et al, 2012; Fliegel et al, 1979; Ralston, 2008; Reisinger & Crotts, 2009, etc.) focuses mostly on small country samples that do not allow conclusions about global trends.…”
Section: Introductionmentioning
confidence: 99%
“…The homogenization thesis is not new, as it has been through numerous periodic revivals and revisions (Fliegel et al 1979, Sweezy et al 1992. Convergency theorists (e.g.…”
Section: Homogenizationmentioning
confidence: 99%